Use of High Quality Forages to Build Climate Resilient Livestock Production Systems - Avril, Dean (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Mr. Dean Avril, Climate Smart Agriculture Officer, World University Service of Canada (WUSC Caribbean) - St. Lucia